Optimization and stabilization ofa cyanidin-3-O-glucoside rich extract obtained from fruits of Arbutus unedo L.. - Jiménez López, Cecília (2018)
Currently, there is a tendency for consumers to choose more natural foods [l]. Anthocyanins are secondary metabolites ofplants that have aroused industry attenüon for its coloring potential combined with confirmation ofvarious beneficiai efFects to human health [2]. However, due to their very sensitive chemical structure to several factors such as temperature, pH, oxygen and light, studies that allow its stabilization are indispensable [3]. This work aimed to study the stability of an extract obtained from Arbutus unedo L. fruits, considering 3 variables (time, temperature and pH) in aqueous solution by analyzing the content of anthocyanins. The extract was obtained by a heat-assisted extraction technique, with the optimal condiüons of 5 minutes, 90°C, 80% ethanol and 15 g/L solid/liquid ratio, obtained after an optimization process by applying a response surface methodology. The identification of three anthocyanin compounds (cyanidin- 3-0-glucoside as the major molecide) was performed by HPLC-DAD-ESI/MS, and revealed the foUowing responses, 60.9 %, with a total anthocyanin content of 500.9 ^ig/g of dry fruit and 800.9 ^ig/g of extract. Moreover, the extract was analyzed in terms of its antioxidant, antimicrobial and cytotoxic activity revealing a high bioactive potential. Finally, the anthocyanin-rich extract was stabilized by subjecting it to adverse storage conditions. Time, temperature and pH were the variables considered to evaluate the behavior of the extract and the concentration of anthocyanins from each sample wére the response factors used. In order to describe the responses, mechanical and phenomenological equations were used with a global performing fitting analysis from a multivariable perspective. The results showed that the three analyzed variables exert a direct influence on the responses obtained. It hás been found that increasing pH and T values cause an exponential increase in anthocyanin degradation. In the overall analysis of ali variables, it was concluded that the optimum conditions ofanthocyanins stability were verified at pH <3.5 and T <30 °C for a period of at least 72 h. At the industrial levei this type of studies is indispensable, in order to guarantee the production of functional extracts in the production of high-quality new foods. Therefore, it is essential to find the optimum conditions of its stability and processing.